Peran Public Relations Dalam Pengembangan Budaya Organisasi - Nurfitriani M. Siregar (IAIN Padangsidimpuan, 2021)
AbstractPublic Relations concerns the interests of every organization, be it commercial or non-commercial organizations. What is commonly referred to as Public Relations consists of all forms of communication that are held between the organization concerned and the public or anyone with whom they have contact. Then organizational culture is a value that guides human resources to deal with external problems and adjustment of integration into the company, so that each member of the organization must understand the values that exist and how they should act or behave. So that the role of Public Relations (the stages of fact finding, planning, communicating, and evaluation) fully refers to the managerial approach. then Public Relations management can be formulated as a process of a group of people coordinating, leading certain activities to achieve common goals.Keywords ; Public Relations, Organizational Culture